Developing Visual Identity to Strengthen Brand Awareness: A Design Thinking Approach - Alfias, Fauzi; Hakim, Abdurrahman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to develop a visual identity for Studio Grafikku, a graphic design service business, to strengthen brand awareness and improve customer recognition through a consistent and distinctive branding system. Design/Methodology/Approach – This study employs a descriptive qualitative research approach. Data were collected through interviews, observations, and documentation. The Design Thinking method was applied to identify customer preferences and develop an appropriate visual identity design. The analysis focused on key branding elements, including logo, color, typography, brand name, and graphic elements, as well as their application across various branding media. Findings – The results show that Studio Grafikku requires a standardized visual identity to improve brand memorability and customer trust. The developed visual identity consists of a logo, color palette, typography, brand name, and supporting graphic elements that align with customer expectations. These elements were implemented across branding media, including social media platforms, websites, and advertisement videos, creating a more consistent and recognizable brand image. Originality/Value This research is original in applying a Design Thinking approach to develop a complete visual identity system for a local graphic design service brand. The findings provide practical value by offering a structured framework for improving brand awareness through cohesive visual branding strategies.